(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
The experiment was developed in the farm Barcelona of the Llanos University, the objective was to determine the in vivo digestibility Boehmeria nivea graud to demonstrate the nutritional quality of this forage. Sixteen rabbits were used, with average weight 3.200 ± 100 grams, they were divided into 4 groups, they were housed in cages, the diets fed were: Treatment 1: 100% B. nivea diet was ad libitum (T1), Treatment 2: B. nivea ad libitum and 0.5% of body weight (BW) in commercial concentrate (CC) (T2), Treatment 3: B. nivea ad libitum and 1% of body weight (BW) (T3) and Treatment 4: B. nivea ad libitum and 1.5% of body weight (BW) (T4). The Dates were collected during 14 days of which were four days of food adaptation and ten sample collections. The design was completely randomized with ten replications and 4 treatments. The variables evaluated were: forage intake, feces excretion, digestibility: Dry matter (DM), protein, fat, nitrogen-free extract (NFE), crude fiber (CF), % total digestible nutrients (TDN) and calculations: digestible energy (DE) and metabolizable energy (ME). The associated digestibilities of dry matter, protein and NFE were lower (p <0.05) in T1, while the fat was similar in all treatments. It was shown that the increase in concentrate has a directly proportional relationship with the increase in the percentage of NDT and the associated digestibility of DM and protein.